Factors Affecting the Auditor’s Independence: Referring to the Provision of Management Advisory Services (Case Study on 4 Certified Public Accountant in Malang City) - Pratama, Ade Setia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The development of CPAs nowadays affects the needs of audit service of clients. They cannot be separated from the role of auditors. Therefore, auditors must be independent in doing their job, including MAS (Management Advisory Service) to improve the quality of their service. The provision of this service can cause auditors to work outside the standard and professional code of ethics that will harm concerned parties. The objective of this research is to get accurate information about factors that affect the independency of auditors during the provision of MAS. Based on past events, independency of auditors becomes the attention of people, particularly in this time, so many criminal cases caused by the auditor’s that can be relieve the client’s trust. The technique of data gathering of this minor thesis is interview technique carried out with four CPAs registered in Malang, represented by one auditor each. The result of this study showed that the excessive knowledge of auditors about clients affected the independency of auditors in providing MAS. The aspect of auditors’ knowledge about clients directly related to data gathering process by auditors through interview and direct sharing. Thus, the intensity of communication between both parties increased the chance for auditor as professionals to work astray from standards and professional code of ethics.Keywords: Auditor Independency, Management Advisory Service, Emotional Relationship, Auditor Responsibility and Ethical code of Accounting Professions